Book Reviews. Issue 2 (1st September 2019) - McKinney, Mark; Howell, Jennifer; Smith, Ross William; Miranda Barreiro, David
Abstract : David Kunzle, Cham: The Best Comic Strips and Graphic Novelettes, 1839–1862 (Jackson: University Press of Mississippi, 2019). 566 pp. ISBN: 978-1-4968-1618-4 ($90) Tatiana Prorokova and Nimrod Tal, eds, Cultures of War in Graphic Novels: Violence, Trauma, and Memory (New Brunswick, NJ: Rutgers University Press, 2018). 237 pp. ISBN: 978-0-8135-9095-0 ($29.95) Stephen E. Tabachnick, ed., The Cambridge Companion to The Graphic Novel (Cambridge: Cambridge University Press, 2017). 244 pp. ISBN: 978-1-107-51971-8 (£21.99) Louie Dean Valencia-García, Antiauthoritarian Youth Culture in Francoist Spain: Clashing with Fascism (London: Bloomsbury Academic, 2018). 248 pp. ISBN: 978-1-350-03847-9 ($114)